Strategies for managing epithelial ovarian cancer in elderly patients: a comprehensive review - Gupta, Sumedha; Kalwaniya, Dheer Singh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
The management of epithelial ovarian cancer in elderly patients presents distinct challenges due to age-related factors and comorbidities. Developing optimal strategies requires a careful balance between treatment efficacy and the potential side effects. This review aims to evaluate current management approaches specifically tailored to elderly patients with epithelial ovarian cancer. It focuses on the effectiveness and safety of various treatments, including surgery, chemotherapy, and targeted therapies, and considers how age-related factors influence treatment decisions and outcomes. Additionally, the review explores the importance of geriatric assessment and supportive care in optimizing treatment for this demographic. The findings suggest that managing epithelial ovarian cancer in elderly patients demands a multifaceted approach that considers both the effectiveness of the treatment and the patient's overall health and quality of life. By recognizing and addressing the unique needs of elderly patients, clinicians can refine treatment strategies, thereby improving outcomes for this vulnerable population. This approach emphasises the importance of individualized care that is responsive to the specific challenges posed by ageing and associated comorbidities, ultimately leading to better health outcomes for elderly patients with epithelial ovarian cancer.